2020
DOI: 10.5326/jaaha-ms-6863
|View full text |Cite
|
Sign up to set email alerts
|

Myxosarcoma Associated with the Kidney in a Cat: Case Report

Abstract: A 12 yr old spayed female domestic shorthair with a history of lethargy, anorexia, and a pendulous abdomen was referred after a cranial abdominal mass was palpated on physical examination. Thoracic radiographs and an abdominal ultrasound revealed a mass associated with the kidney and moderate hemoperitoneum. Exploratory laparotomy revealed abdominal hemorrhage originating from a right renal mass that was adhered to the caudal vena cava. Following a right nephrectomy, histopathology diagnosed the mass as a peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 6 publications
1
11
1
2
Order By: Relevance
“…The owners last reported that the patient had been doing well at 6 months post‐surgery, and the cat was lost to follow‐up thereafter 12 . A similar clinical outcome was observed in a case report of a feline perirenal/renal myxosarcoma 11 . A 12‐year‐old spayed female domestic shorthaired cat presented for evaluation of a large and firm palpable mass in its cranial abdominal cavity.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…The owners last reported that the patient had been doing well at 6 months post‐surgery, and the cat was lost to follow‐up thereafter 12 . A similar clinical outcome was observed in a case report of a feline perirenal/renal myxosarcoma 11 . A 12‐year‐old spayed female domestic shorthaired cat presented for evaluation of a large and firm palpable mass in its cranial abdominal cavity.…”
Section: Discussionsupporting
confidence: 75%
“…Positive immunoreactivity to vimentin and negative immunoreactivity to cytokeratin of the neoplastic cells confirmed a mesenchymal origin, and based on these collective findings, a diagnosis of a well‐differentiated renal myxosarcoma was made. Fourteen months postoperatively, no evidence of metastatic disease or tumor recurrence were seen in this patient based on repeated staging diagnostics that included thoracic radiographs and an abdominal ultrasound 11 …”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations